أثر قطعية المباحث اللفظية على المنهج المعرفي الأصولي: الرازي والشاطبي نموذجان: Al-Razi and al-Shatibi on the Impact of Philosophy on the Definitive and Hypothetical Aspects of the Juristic Deductive Method - Abdullah Naseh `Ulwan, `Ammar (Afkar: Jurnal Akidah dan Pemikiran Islam, 2016)
Muslim scholars agreed to accept an epistemological shari`ah method as the “principles of Islamic jurisprudence” (Uṣūl al-Fiqh). Each school of thought has its own Islamic legal principles as the epistemological criteria. Therefore, the most of influential Islamic sects on the Islamic thought have the principles of Islamic law as their own epistemological method; and the principles of Islamic law represent the epistemological method of the different schools of thought among Muslims. Philosophy has an influence on the development and formulation of this epistemological method, particularly in classifying the definitive (final) or even hypothetical deductive in the original sources of Islamic law. The philosophers have argued that the deduction of the finality (definitive) is a form of rational inferences and is not empirical statements. Based on this classification, a hypothesis formulation can be achieved through the deductive methods. Al-Razi pioneered the debate on the hypothetical deduction in his book, al-Mahsul. He argued that the definitive aspect does not merely exist in the literal discussions. However, al-Shatibi, a thinker, who was the first person, introduced this discussion in al-Muwafaqat. He argued that "the principles of Islamic law" are definitive and the religious knowledge is equivalent to the rational knowledge. He thus believed that the definitive aspects of the principles of Islamic law are derived from the philosophical method called induction. This induction method can be benefitted in legal matters, as well as in arguments in the prohibition of the differences that are only limited to a few matters of ijma`. Therefore, it makes a disagreement of opinions is justifiable in every legal matter.